“ESTUDIO COMPARATIVO: DISTORSIONES COGNITIVAS EN LOS ESTUDIANTES DE LA FACULTAD DE CIENCIAS DE LA EDUCACIÓN HUMANAS Y TECNOLOGÍAS.” - Quito Cazorla, Yajaira Mirella (2020)
This research carried out the Comparative Study of Cognitive Distortions in the students of Human Education Sciences and Technologies Faculty. During the life of every human being, the conception of various schemes of the world prevailed, bombarded by irrational thoughts that were automatically incorporated into the brain, storing them as part of their daily living. To fulfill the study's objective, to analyze the student's cognitive distortions, it used research with a quantitative approach, of non-experimental design, of a correlational type. For the primary objective and the field location, the technique used was a Psychometric Test with its instrument: The Automatic Thoughts Inventory Test, where the different unconscious thoughts were evidenced, evaluated by 15 Cognitive Distortions, through 45 questions. The sample was made up of 82 sixth semester students from the Educational Psychology and Biology-Chemistry and Laboratory Schools. The Automatic Thoughts Inventory test results showed that the students presented an equitable assessment scale of polarized thinking. Finally, it was identified that more and less frequently, they presented two types of cognitive distortions; Emotional Reasoning and Fallacy of Reason.